Single-valued and multi-valued Meir-Keeler type operators - Petruşel, Adrian (Rev. Anal. Numér. Théor. Approx., 2001)
The purpose of this paper is to present several xed point results for some single-valued and multi-valued Meir-Keeler type operators.